Investigation of self-attenuation of 210Pb (46 keV) gamma ray in sediment, certified reference material and high-density minerals: Implication to precise measurement of 210Pb. (August 2022) - Denny, Max; Baskaran, Mark; Walsh, Chelsea; Ibrahim, Vanessa
Abstract: High resolution gamma spectrometry is one of the most widely used techniques in the measurements of environmental level 210 Pb in sediment from coastal and freshwater environments and such measurements are needed to establish 210 Pb chronology for the past 100–150 years. Precise measurement of 210 Pb in sediment and soil requires appropriate self-absorption correction for its low-energy (46.5 keV) gamma radiation due to differences in the matrix between the sample and standard used to calibrate the instrument. Here we report a method that involves precise determination of 210 Pb activity in sediment sample by calibrating the HPGe well detector with RGU-1-IAEA Certified Reference Material for well-defined geometries. A comparison of the 210 Pb activity obtained from gamma-ray spectrometry with that obtained from alpha spectrometry via 210 Po, using 209 Po as yield tracer, indicates good agreement. We propose an empirical relation between the absolute efficiencies and packing densities of sample in a well-defined geometry (cylindrical counting vial) by affecting the count rate of 210 Pb and its progenitor, 226 Ra (via 214 Pb and 214 Bi). The effects of self-attenuation of 46.5 keV ( 210 Pb), for naturally-occurring high-density minerals (apatite, titanite, monazite, and cerite) are evaluated. Specific activity of 210 Pb on apatite measured by alpha and gamma spectrometry are compared. This study is relevant and useful for precise measurements of gamma-emitting environmental radionuclides such as 210 Pb, 7 Be, 137 Cs as well as 226 Ra. Highlights: Self-attenuation for 210 Pb in high-density minerals HPGe-detector is high, 12–38%. The self-attenuation correction for high density minerals is variable for ≥338 keV. Comparison of 210 Pb by α− and γ-spectrometry needed for low 210 Pb activity sample. Empirical relationship between packing density & counting efficiency is established.